Establishment Of Callus And Cell Suspension Culture Of Artemisia Annua L. Of Vietnamese Origin - Chin , Chee Keong (2011)
Callus cultures from three clones of Artemisia annua L. were induced from the leaf explants of axenic plantlets. MS and LV basal media supplemented with 0.5 mg/L BA, 0.5 mg/L NAA and 0.5 g/L casein hydrolysate were used as induction medium. The three clones of A. annua, namely TC1, TC2 and Highland clones, showed difference in callus growth and appearance. MS basal medium was found to be the better callus induction medium as compared to LV basal medium. Generally callus growth was better in terms of biomass yield and friability when induced on MS basal medium than it was on LV medium.